Unvoiced and invisible: on the transparency of white South Africans in post-apartheid geographical discourse - Gustav Visser (Acta Academica, 2003)
Over the past decade South African urban geographers have developed a rich body of research ably narrating the changing spatialities of post-apartheid society. It is the contention of this paper that in mapping this transition the “white” geographies of the apartheid era have merely been replaced by “black” geographies and that situation is frustrating the development of truly post-apartheid geographies since the many-sided dialectic relationships that constitute South African spatialities are being overlooked. Drawing on poverty research as an example, the paper considers ways in which “white South African lives” may be reintroduced to the research practices of South African geographers. To attain this objective it first contextualises the “disappearance” of white geographies with reference to poverty research in South Africa. It then suggests some reasons why South African geographers have failed to offer any analysis of white communities and, in particular, of the marginalised  among them. Its final section provides some pointers to possible research themes that might address this oversight.